BeeLife: a mobile application to foster environmental awareness in classroom settings - Stock, Adrian; Stock, Oliver; Mönch, Julia; Suren, Markus; Koch, Nadine Nicole; Rey, Günter Daniel; Wirzberger, Maria (Frontiers in Computer Science, 2024)
Significant threats to our environment tremendously affect biodiversity and related gains. Particularly wild bees actively contribute by pollinating plants and trees. Their increasing extinction comes with devastating consequences for nutrition and stability of our ecosystem. As most people lack awareness about those species and their living conditions, we introduce an intervention consisting of a mobile app and related project workshops that foster responsibility already at an early stage in life. Drawing on principles from multimedia learning and child-centered design, six gamified levels and accompanying nature-based activities sensitize for the importance of wild bees and their role for a stable and diverse ecosystem. A pilot evaluation across three schools, involving 44 children aged between 9 and 12, included a pre-, post-, and delayed post-test. Results hint in a promising direction: Most children perceived the app as intuitive, engaging, and visually appealing, and sustainably benefited from our intervention in terms of retention performance. Future extensions might include adaptive instructional design elements to increase observable learning gains.